477 Three cases of Kawasaki disease developed at young age and with a long term follow-up. (8th December 2021) - Zagarese, Giorgia; Varriale, Alessandro; Pesarini, Gabriele; Cristofaletti, Alessandra; Sandrini, Camilla; Ribichini, Flavio Luciano; Prioli, Maria Antonia
Abstract: Kawasaki disease is a relatively new disease and it took years since its first discovery to find and establish precise diagnostic and therapeutic indications. We report three cases of Kawasaki disease diagnosed between 1976 and 1993, which developed vascular complications and which were followed up for more than 20 years. The first case involved a 45-year-old woman who was first diagnosed with Kawasaki disease at age 3 years old. Her condition was complicated in the acute phase by a myocardial infarction and by the development of an apical aneurysm. The second case involved a 30-years-old woman who was first diagnosed with Kawasaki disease at age 6 months. The disease was complicated by coronary aneurysms and by right coronary artery occlusion. The third case involved a 29-year-old male who received a diagnosis of Kawasaki disease at age 1 year old. Echocardiography in the acute phase showed coronary aneurysms. One year later a new echocardiography revealed a thrombosis of the right coronary artery without myocardial infarction. The coronarography confirmed the coronary aneurysms and the thrombosis. All three cases were treated with a medical therapy and were followed up with periodic imaging exams, stress tests, 24-h Holter monitorings and cardiological check-ups. With these three case reports we have highlighted the possibility of finding a population of adult patients who may come to medical attention for acute events, such as myocardial infarction, presenting complicated, and disastrous angiographic pictures: it is plausible that such a population, in addition to cardiovascular risk factors, may have developed a KD in the years of lacking diagnostic and therapeutic options.